(3MGTjI Ydj Ndjd GdbRhjfj Ydi cJGH YOI GdCUhd ddTjN GdWhSjs - (3GdNdjdj GdbRhjfj, CHh jYdi, Ndjd Hf YHO Gddg Hf CMeO Hf EHQGgje GHf GdNdjd, J (B446 (3g`s
(3ChdgG (B:s
.. (3gPG MO CUhd Gdabg HGYJHGQ eYfi GdEVGaj Gdefbhd Yfg hGdCUhd LeY CUd hgh eG jHJfj Ydjg GdTjA hGdbGYOI GdcdjI hGdOdjd hZjQ Pdc hEPG CVja Edi GdYdhe hGdeSGFd (B..s
(3BNQgG (B:s
.. (3dcf jbOQ aj GdChd eVGa hGdJbOjQ cd eHGM YdI JQc GdMQGe Ch SHHg Ch fMh Pdc hGNJU GdJbOjQjI dXghQ YOe UMI GdGNJdGa GdKGfj haj gPG GdGSJOdGd (B..s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2/319s
(3GdPQjYI (B6/ (3bHd (B402s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs